“The curriculum just flows” – An examination of teachers’ understandings and implementation of Te Whāriki pre–2017 - Cameron M; Aspden K; Smith P; McLaughlin T (Wilf Malcolm Institute of Educational Research, The University of Waikato, 2023)
The revision of Te Whāriki, the New Zealand Early Childhood Curriculum Framework, in 2017 offered a unique opportunity to gain understanding of the ways teachers in Aotearoa New Zealand think about and enact curriculum in their daily practice. As researchers we were intrigued as to the ways teachers conceptualised the role of curriculum in practice and whether the revised curriculum would generate changes in curriculum implementation. We undertook a research project to capture data about teachers’ engagement with, and use of, the curriculum framework, as well as their beliefs about curriculum in the context of early childhood education (ECE). Data collection was designed to focus on two points in time: in 2017 prior to the launch of the revision, with plans to repeat collection after several years with the revised curriculum in effect. Findings reported here draw on interviews conducted with teachers working with Te Whāriki (Ministry of Education, 1996) before the revised framework was released. The findings revealed a range of understandings about the meaning of curriculum and the role of curriculum in guiding teachers’ enacted practice. Implications for supporting ongoing efforts of enactment and implementation of ECE curriculum are discussed.
Keywords: Curriculum; Te Whāriki; teacher practice; curriculum implementation; early childhood curriculum